Mesoporous silica-based abrasion resistant antireflective (AR)-cum-hydrophobic coatings on textured solar cover glasses by a spray coating technique. Issue 7 (4th March 2022) - Manna, Srikrishna; Naskar, Milan Kanti; Medda, Samar Kumar
Abstract : The present work describes the fabrication of functionalized mesoporous silica based antireflective-cum-hydrophobic coatings on textured solar cover glasses via a spray-coating technique exhibiting enhanced photo-current density. Abstract : The present work describes the fabrication of functionalized mesoporous silica based antireflective- cum -hydrophobic coatings on textured solar cover glasses via a spray-coating technique; the fabricated coatings exhibit good abrasion resistance. The thicknesses of the AR and hydrophobic layers have been varied in the ranges of 350–500 nm and 30–45 nm, respectively. The application of a bilayer coating on textured solar cover glass resulted in a significant enhancement of ≥4% in the average solar transmission in the wavelength range of 400–1100 nm. A hydrophobic coating with self-cleaning properties was designed on the mesoporous silica coating, and it exhibited an enhancement of the photo-current density (mA cm −2 ) of 4.65% under simulated solar light of 1 sun with a maximum output power enhancement of ≥4% based on I – V (ampere-volt) characterization. After 50 cycles of sandpaper (80 mesh) abrasion testing of the coated solar cover glass, its water contact angle value was reduced from 130° to 105°, and 50 h UV radiation exposure testing confirmed that there were no significant changes in the coating quality. These results indicate the good durability, abrasion resistance, and AR/hydrophobic properties of the coatings.